An iterative method for solution of nonlinear operator equation - Bường, Nguyễn (Journal of Computer Science and Cybernetics, 2016)
In the note, for finding a solution of nonlinear operator equation of Hammerstein’s type an iterative process in infinite-dimentional Hilbert space is shown, where a new iteration is constructed basing on two last steps. An example in the theory of nonlinear integral equations is given for illustration.